Advertising and the Republic of Letters (2023)
ABSTRACT: Towards the end of the 19th century, in Colombia, men of letters dominated the cultural and political world, so it can be said that this country was the Republic of Letters. However, the economic and social changes that occurred with the turn of the centur y allowed new groups, such as entrepreneurs, to begin disputing political power, and for this, the use of images rather than words was decisive. This article analyzes what happened to letters and images when they functioned simultaneously in the 1920s, taking the Antioquia case as a reference. There, Humberto Chaves, a master painter who also worked as a graphic designer and advertiser, was respons ible for creating images of the modern, which the entrepreneurs sought to use to dominate both the market and the national political sphere.